ANALISIS PARTISIPASI ANGGARAN TERHADAP BUDGET SLACK: PERSEPSI KEWAJARAN PROSEDURAL DAN DISTRIBUTIVE, KEPERCAYAAN MANAJERIAL, DAN KOMITMEN TUJUAN ANGGARAN SEBAGAI FAKTOR INTERVENING - Hardiwinoto Hardiwinoto (MAKSIMUM, 2010)
The aim this research to examine of the relationships between budget participation that influence manager’s propensity to create budget slack: procedural and distributive fairness, managerial trust, and budget goal commitment as intervening variable. The results show that budget participation impacts both procedural fairness and distributive fairness which, affect trust. Both, procedural and distributive fairness, are found to have a significant impact on budget goal commitment, and negatively influences managers’ propensity to create slack. Further analyses indicatethat the direct relationship between budget participation and manager’s propensity to create slack was insignificant, which suggests that fairness and goal commitment mediate the relationship between budget participation and manager’s propensity to create slack.Keywords: Budget, Distributive Fairness, Procedural Fairness, Trust, GoalCommitment, Budget Slack.